The presence of a patient’s voice in the care process: Implications for patient-centeredness - Sobane, Konosoang; Magampa, Mmakotsedi (Stellenbosch Papers in Linguistics Plus, 2016)
A patient-centred approach to care is increasingly recognised as the hallmark of adequate healthcare delivery since it allows a holistic approach to care. Although there is no agreed-upon definition of patient-centred care, literature on this subject recognises effective communication and patient participation as necessary factors for the achievement of patient-centred care. Despite ample literature on the value of patient-centred care and the patient’s voice in it, there is very limited literature on its achievement in linguistically-diverse consultations. There is even less literature on the subject based on research conducted in Sub-Saharan Africa, where multilingual healthcare systems are prevalent and there is a need for policy interventions to regulate such systems. This paper traces the presence or silence of the patient’s voice in linguistically-diverse consultations and the implications that it has for achieving a patient-centred approach to care. The findings suggest that the language barrier submerges the patient’s voice at many of the points of the care process. Where it is visible, it is not on the basis of participation in decision-making, but in responding to questions asked. The paper therefore makes recommendations for a strategic communication framework that will enhance the presence of the patient’s voice in language-discordant consultations.